THE EFFECT OF GADGETS ON STUDENTS’ LEARNING OUTCOMES IN IT SUBJECT AT GRADE V SD ST. ANTONIUS BANGUN MULIA MEDAN - Melfa Norestina Sidebang; Rumiris Lumbangaol; Ester J Simarmata; Patri Janson Silaban (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The results of data analysis, hypothesis testing, and discussion concluded that this study aimed to determine the effect of gadgets on students’ learning outcomes in the IT subject at grade V of SD St. Antonius Bangun Mulia Medan in the academic year 2020/2021. The population of this study consisted of 55 students, and all students were selected as the sample. A quantitative method with a survey design was used to obtain the required data. The samples were selected using a random sampling technique. Data were collected through observations, questionnaires, and document studies. The hypothesis was tested using correlation analysis and a t-test. The results showed that the initial average score of students’ learning outcomes was 66.90, which was categorized as fair with a percentage of 32.72%. After using gadgets in learning, the average score of students’ learning outcomes increased to 85.36, which was also categorized as fair with a percentage of 34.54%. Furthermore, the hypothesis testing results showed that rcount = −0.169 and tcount = −1.248, while ttable = 1.673 at a significance level of 5%. Since tcount < ttable (−1.248 < 1.673), H0 was accepted and Ha was rejected. This indicates that gadgets had no effect on the learning outcomes of fifth-grade students at SD St. Antonius Bangun Mulia Medan.